Bmi1 deficiency exacerbates hyperoxia-induced acute lung injury in mice - Hernández-Cuervo, Helena; Soundararajan, Ramani; Patil, Sahebgowda Sidramagowda; Breitzig, Mason T.; Alleyn, Matthew; Narala, Venkata Ramireddy; Lockey, Richard; Galam, Lakshmi; Kolliputi, Narasaiah (Frontiers in Physiology, 2025)
IntroductionAdministering high levels of oxygen is a life-sustaining measure in critically ill lung subjects. However, prolonged hyperoxia exposure increases reactive oxygen species (ROS) that exacerbate oxidative stress, mitochondrial dysfunction, respiratory failure, and cell death. Mitochondria play a critical role in hyperoxia-induced acute lung injury (HALI). The specific role of the Polycomb Repressive Complex 1 protein BMI1 (B cell-specific Moloney murine leukemia virus integration site 1) in mitochondrial damage remains unknown.MethodsBmi1 knockout mice (Bmi1−/−) and their wild-type (WT) littermates were exposed to normobaric hyperoxia using oxygen concentrations of 95-100% for 48 h to assess BMI1 function in HALI. This research included the estimation of protein and gene expression, live mitochondria isolation, Oxygen consumption rate measurement, histomorphology analysis, capillary assessment, and dynamic lung function evaluation.ResultsMice lacking Bmi1 versus WT exposed to hyperoxia exhibited hallmarks of human acute lung injury (ALI) such as increased lung permeability, alveolar edema, hemorrhage, interstitial thickening, and infiltration of immune cells; and alterations in lung mechanics, including increased elastance and decreased lung compliance.DiscussionBmi1−/− mice exhibit increased mitochondrial damage, increased oxidative stress, and significant changes in protein markers related to mitophagy compared to WT mice. Our results indicate that Bmi1−/− mice are susceptible to HALI, and the damage increases in those mice compared with their WT littermates.